Avaliação da aprendizagem realizada pela tutoria online a partir das interações nos fóruns de discussão no ambiente virtual de aprendizagem - Silva, Rose Madalena Pereira da (2017)
This study approaches the evaluation of learning from the interactions in the virtual learning environment (AVA) carried out by the online tutoring in discussion forums of three courses in Distance Education (EaD) developed in AVA / MOODLE of the Open University of Brazil ( UAB), linked to UFAL, with the purpose of studying the evaluation of the learning carried out by online tutoring in the AVA discussion forums. The question that opens the research is: how is the evaluation of the learning in the forums by the online tutoring from the interactions in AVA? The methodology followed was based on the qualitative approach with exploratory category of data and the type of research case study with the purpose of analyzing the type of evaluation of the learning carried out by online tutoring. The objective of the research was to analyze the way in which the evaluation of the learning realized by the online tutorial using the didactic resources available in AVA specifically in the tool / forum resource. The specific objectives were: to identify in the interactions of the forums how the evaluation of the learning carried out by the online tutor and to describe how the online tutor conducts the evaluation process of learning in the AVA. To collect data, a questionnaire was applied to 10 online tutors and the interactions of these tutors in the disciplines forums of the three Portuguese / Portuguese, Mathematics and Pedagogy courses in the period of 2015.1. The next moment was the analysis and interpretation of the data considering the objectives of the research. The observed results indicate that the evaluation carried out by the online tutoring is focused on the summative aspects, even in some moments the interventions are directed to the formative evaluation. It was also observed from the research that online tutors do not recognize themselves as subjects that evaluate students' learning in AVA and understand that the function of evaluating learning is only the teacher of the discipline.